Using SQL for data consolidation in R - Vinas Forcade, Jennifer (2018)
Working with multiple data sources implies data cleaning and consolidation prior to analysis. R has become popular among social scientists (Kelley, 2007; Clark, 2014), who are advised to screen data in a “favorite spreadsheet program” (Muenchen, 2011:21), before importing it to R. This way, users avoid typing in the R console and are supported by a graphical user interface. Even for experienced R users, querying/ retrieving data from multiple large sources takes a lot of computing power, which is better handled by SQL language (Table 2; KeyCentrix, 2015).